EFFECTS OF GROWTH CONDITIONS ON SIDEROPHORE PRODUCING BACTERIA AND SIDEROPHORE PRODUCTION ISOLATED FROM AGRONOMIC FIELD OF DIFFERENT ZONES OF BILASPUR DISTRICT OF CHHATISHGARH - Pratibha Singh Chandel (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Siderophores are synthesized and secreted by many bacteria, yeasts, fungi, and plants for Fe (III) chelation. Eight microbial isolates were tested for their ability to produce siderophores, with Pseudomonas flurescens showing the highest production at 72%, followed by Azospirillum lipoferum at 63%. Microbial isolates producing siderophore significantly improve nodulation in green gram, offering ecological advantages and encouraging their use as inoculants with root nodule bacteria. The amount of total iron (10–17 M) in the soil is toolow to support microbial growth (10–7 M); siderophoresthat bind to Fe3+, transport it back to microbial cells and make it available for microbial growth (Meyer, 2000). Within the graminaceous plants, maize is also classified as strategy II plant that acquires iron by the release of phytosiderophores in the rhizosphere coupled to induction of high affinity system for iron-phytosiderophore complex that transports it across the plasma membrane of root cells (Marschner and Roemheld, 1994)